2000
DOI: 10.1089/cbr.2000.15.625
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ovarian Clear Cell Carcinoma: Complete Remission after Radiation in Combination with Hyperthermia; A Case Study and in vitro Study

Abstract: Since clear cell carcinoma of the ovary does not respond to conventional platinum-based chemotherapy, the prognosis of recurrent tumors is especially poor. In a 51-year old female who underwent surgery for clear cell carcinoma of the ovary, a solitary metastatic carcinoma developed in the pelvic cavity seven months after the initial surgery. The patient underwent a whole pelvic irradiation at a total dose of 65 Gy combined with hyperthermia. Complete remission was achieved 46 months after treatment. A study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…However, the anticancer drug sensitivity test using this cell line suggested that the effects of these anticancer drugs are limited. In contrast, with the radiation sensitivity test, the ID 50 value for TAYA cells was 1.8 Gy, which was consistent with our previous results in uterine cervical cancer cell lines [7]. It is well known that patients with uterine cervical cancer are highly sensitive to radiation, and it is notable that the radiosensitivity of TAYA cells was equivalent to that of uterine cervical cancer cell lines.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the anticancer drug sensitivity test using this cell line suggested that the effects of these anticancer drugs are limited. In contrast, with the radiation sensitivity test, the ID 50 value for TAYA cells was 1.8 Gy, which was consistent with our previous results in uterine cervical cancer cell lines [7]. It is well known that patients with uterine cervical cancer are highly sensitive to radiation, and it is notable that the radiosensitivity of TAYA cells was equivalent to that of uterine cervical cancer cell lines.…”
Section: Discussionsupporting
confidence: 90%
“…An establishment of effective treatment methods for clear cell adenocarcinoma of the ovary is needed. We recently reported on a patient with recurrent clear cell adenocarcinoma of the ovary in whom complete remission was obtained by a combination of radiotherapy and hyperthermia [7]. We established a new cell line from ascites of the patient with clear cell adenocarcinoma of the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a patient was reported with clear cell carcinoma of the ovary in whom complete remission was obtained by a combination of radiotherapy and hyperthermia (12). Moreover, also an established clear cell adenocarcinoma cell line turned out to be rather resistant to chemotherapy with cisplatin, irinotecan, paclitaxel and gemcitabine whereas it was very sensitive to Á-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the potential roles for radiotherapy in the consolidate treatment and as salvage therapy following chemotherapy failure remain controversial (11). There are examples where radiotherapy has proven to be successful (12) and where a combination of radiotherapy and hyperthermia led to the complete remission of an ovarian clear cell adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation